SMARTPHONE ADDICTION, ATTENTION DECLINE, AND CHANGES IN EMOTIONAL STATE - Choriqulova F. E.; Nigmatullayeva D. J (The Conference Hub, 2025)
In recent years, the deep integration of smartphones into everyday life has led to the emergence of new psychohygienic problems associated with their excessive use. Smartphone addiction has been confirmed by numerous epidemiological and clinical studies to be associated with reduced attention, emotional instability, and increased anxiety and depressive symptoms.